2018
DOI: 10.1021/acs.energyfuels.8b03416
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Australian Saltbush

Abstract: Hydrothermal carbonization (HTC) is a thermochemical process, wherein biomass is subjected to high-pressure, high-temperature subcritical water to improve the combustion characteristics of biomass as a solid fuel. Australian saltbush was subjected to HTC at three temperatures (200, 230, and 260 °C) and four holding times (0, 15, 30, and 60 min) using a custombuilt batch reactor. The resultant hydrochars demonstrated improved higher heating values (HHVs), with temperature more influential than time. At the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…C=O carbonyl groups (1730–1698 cm –1 ) are also reduced with increasing temperature, likely as a result of decarboxylation reactions of the cellulose, leading to the production of formic acid and CO 2 . These reductions, combined with the shrinkage of the 3400 cm –1 peak, indicate a substantial loss of oxygen-containing functional groups, leading to an overall purging of oxygen from the feedstock . The ability to remove oxygen from a given fuel is an important asset of HTC and is partly responsible for boosting the higher-heating value of the hydrochar …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…C=O carbonyl groups (1730–1698 cm –1 ) are also reduced with increasing temperature, likely as a result of decarboxylation reactions of the cellulose, leading to the production of formic acid and CO 2 . These reductions, combined with the shrinkage of the 3400 cm –1 peak, indicate a substantial loss of oxygen-containing functional groups, leading to an overall purging of oxygen from the feedstock . The ability to remove oxygen from a given fuel is an important asset of HTC and is partly responsible for boosting the higher-heating value of the hydrochar …”
Section: Resultsmentioning
confidence: 99%
“…The HTC reaction was performed using a stainless steel custom-built reactor with an electronically heated fluidized bed (Techne, model: SBL-2D) as a heat source, according to previously published methods. 9 In brief, a stainless steel reactor tube with an internal volume of 30 mL, equipped with a thermocouple, pressure transducer, safety valve, and a pair of hand-operated ball valves, was filled to 80% maximum capacity with a biomass-water slurry with a 15% solids loading. The reactor was sealed, and gaseous oxygen within the reactor was purged with nitrogen, resulting in a completely nitrogenous reaction atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 In recent years, many researchers have carried out hydrothermal carbonization of various biomasses and analyzed the properties of hydrochars. Keiller et al 20 produced and analyzed hydrochars of Australian saltbush, and the results indicated that the hydrochars possessed numerous similarities to fossil coal, such as higher heating values (HHVs), ratios of C/O and H/C, contents of the volatile matter (VM), fixed carbon (FC), and ash. Samaksaman et al 11 investigated the fuel characteristics of the hydrochars from macadamia nut shells and found that the HHV of the solid product ranged from 22 to 27 MJ/kg.…”
Section: Introductionmentioning
confidence: 99%